Biblical exegesis in the apostolic period - Longenecker, Richard Norman, 1930- (Grand Rapids, MI Eerdmans, 1975)
Includes bibliographical references and indexes.
Keywords: Bible -- criticism, interpretation, etc. -- history -- early church, ca.30-600.; Bible. N.T. -- relation to the Old Testament